2019
DOI: 10.1002/pchj.277
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fantastical television content on Chinese preschoolers’ executive function

Abstract: Literature has indicated the mixed impact of television content on the executive function (EF) of preschoolers. This study investigated the short‐term impact of TV fantastical events on children's EF performance and whether these impacts were different between boys and girls. This study included 143 preschoolers (Mage = 5.88 years, SDage = 0.32 years) and their parents. Participating children were randomly assigned to three groups to watch cartoons of high‐fantasy, mid‐fantasy, and low‐fantasy, and then reques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Carey suggested that even very young children had a strong expectation about how things should happen [31]. Events that do not conform to children's expectations may overload information processing and weaken the children's subsequent cognitive behavior [50]. Second, the attention and processing of fantastical events might deplete the neurotransmitters in the lateral prefrontal cortex and reduce children's availability for subsequent cognitive tasks [51].…”
Section: Discussionmentioning
confidence: 99%
“…Carey suggested that even very young children had a strong expectation about how things should happen [31]. Events that do not conform to children's expectations may overload information processing and weaken the children's subsequent cognitive behavior [50]. Second, the attention and processing of fantastical events might deplete the neurotransmitters in the lateral prefrontal cortex and reduce children's availability for subsequent cognitive tasks [51].…”
Section: Discussionmentioning
confidence: 99%
“…Physically impossible and hence fantastical events are commonly used in child-directed TV and videos. Comprehension of fantastical events may be cognitively taxing due to their novelty and rarity in daily life, resulting in excessive consumption of resources [115][116][117]. It has been suggested that executive functions and processing fantastical events may rely on the same cognitive resources; thus, watching fantastical events may have immediate negative effects on executive functioning (e.g., [118]).…”
Section: Fantastical Contentmentioning
confidence: 99%
“…It has been suggested that executive functions and processing fantastical events may rely on the same cognitive resources; thus, watching fantastical events may have immediate negative effects on executive functioning (e.g., [118]). To test this hypothesis, a series of studies investigated the short-term effects of watching fantastical content on young children's executive functions and reported poorer performance on executive function tasks after watching fantastical events [115][116][117]119]. These findings were complemented by higher activation of the brain and frequent and shorter eye fixations while watching a higher number of fantastical events, potentially indicating more cognitive effort [116].…”
Section: Fantastical Contentmentioning
confidence: 99%
“…In some studies, children's involvement in tasks during free play or direct testing has been used to measure attention [ 24 ]. Another substantial portion of these studies adopted the model of EF proposed by Miyake et al [ 25 ], which divided EF into three components: inhibitory control (the ability of a person to inhibit dominant or automatic responses in favor of less prominent data), working memory (the capacity to hold and manipulate various sets of information) and flexibility (shifting attention) [ 10 , 26 , 27 ]. Alternatively, some studies have measured EF through two dimensions: "hot" and "cool" [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%